A study on perception of employees TM on factor that influencing foreign direct investment in Telekom Malaysia (Global) / Nurul Asyikin Abdul Ghani - Abdul Ghani, Nurul Asyikin (2011)
This project paper is prepared as a partial fulfillment of the Bachelor of Business Administration (Hons) International Business. Due to this matter, I have determined the topic of my research “A study employee perception on Factor that influencing foreign direct investment” This project paper contain five chapters. It includes an introduction, literature review, research methodology and design, data analysis and interpretation and conclusion and recommendation. The purpose of this study is to identify the best factor that influencing foreign direct investment. This study was conducted throughout the duration of five month practical training. The study generated 132 respondent from Telekom Global. All the responses from the questionnaires given to the respondents were statistically analyzed with several statistically tool by using SPSS version 18.0. From the analysis, most of the respondent is female .On top of that, they are mostly aged between 41 to 50 years old .82 respondent are work with TM Global more than 8- 12 years. From the analysis too, the researcher can conclude that all the two objectives of the study were achieved and it been showed by Cronbach’s Alpha Analysis, Descriptive Statistic, and Pearson Correlation. According to Pearson correlation only Size of market and geographical location have relationship towards factor that influencing foreign direct investment.